Redes de bibliotecas escolares no Brasil - Rubeniki Fernandes de Limas (2015)
This project is about school libraries networks in Brazil. The school library is viewed as a strategic element for the improvement of education due to its potential impact on the development of literacy and information competence. At the same time, it is a historically precarious institution in respect of infrastructure, and socially undervalued. It is assumed that such precariousness derives from a form of action characterized by isolation from other libraries and by dissociation from their educational context. Unlike this setting its possible to observe a tendency that favors joint action: networks of school libraries are being established and presenting better results. The objective of this research is therefore to understand the structure and functioning of school libraries networks in Brazil. The justification for the research is a lack of national studies in that scenario, being a historically new trend. The methodology of the research was multiple case study, with three functioning networks as samples. The methodological approach was qualitative and exploratory, on the base of comparative method. Data collection was done through documentary research and interviews with network coordinators. The results demonstrated that the networks studied are characterized as library systems. These Networks emerged during the second half of 90's, catalyzed in the context of transformation and even larger movements to renovate the local teaching system. At some point, there was a change of the concept about the library. It changed from the conservation paradigm to that of the library as a learning center. There is a wide range of situations regarding the formalization of the network. It can range from cases with well defined legislation and documentation, to complete lack of formalization. A library coordinator working in the central office of education appears as a key element, as an intermediary between the office and the school library. One of the strengths of the network is the recruitment of librarians, yet the expectation posed on those professionals to perform beyond technical activities is not fulfilled. Results suggest that the networks are just on the starting point, requiring strengthening as systems. This could consolidate the networks structure, so that intermediate and final activities could be improved. In conclusion it can be said that library cooperation is not the main concern, differently from the initial belief. Apparently, networks represent a trend to professionalize the school library. This point would need to be investigated with more detail. The main benefit of implementing the networks was to provide organization to aforementioned aspects, summarized as a concept of the library, support for legislation, budgeting, administrative structure, professionalization, and insertion into public policies. It was found that the differential point between the investigated networks is a more defined advancement in those aspects, though there are still challenges. It is expected that the results allow a broader understanding of the current situation, as well as serve as a basis for further study at some points or even inspire the modeling of new library networks.